Two types of melanopsin retinal ganglion cell in the mouse retina: the regulation of melanopsin expression - Baver, Scott Benjamin, author; Tobet, Stuart, advisor (Colorado State University. Libraries, 2009)
Rods, cones and a subset of retinal ganglion cells (RGCs) that express the photopigment melanopsin are the sensory photoreceptors of the mammalian retina. The light-driven signals that are initiated by the photoreceptors are relayed from the retina to the brain. In addition to the role of light information in regulating the perception of colors, objects and movement, it also controls pupil size and the synchronization of daily physiological rhythms to the day/night cycle. The melanopsin-expressing RGCs, which are intrinsically photosensitive (ipRGCs), contribute especially to these two latter processes. The focus of this dissertation is the ipRGCs of the mouse retina.

While previous evidence has suggested that there are several ipRGC types in the mouse retina, there has been little supporting data to separate these cells into distinct types. Conventional RGC classification is based on a variety of parameters that includes soma size, dendrite branching, and dendrite ramification in the inner plexiform layer (IPL). It has proven difficult to use the same classification scheme for ipRGCs due to their extensive dendritic fields.

Chapter 2 identifies two types of ipRGC in the mouse retina using a mouse in which the tau-lacZ fusion protein replaces the melanopsin protein. These ipRGC types (M1 and M2) differentially project to the suprachiasmatic nucleus (SCN) of the hypothalamus and olivary pretectal nucleus (OPN). In addition, M1-type ipRGC dendrites ramify in the OFF sublamina while M2-type ipRGC dendrites ramify in the ON sublamina of the IPL. To further assess the role of classical photoreceptor pathways in regulating melanopsin expression, transgenic and reporter mouse lines were used and subjected to various lighting paradigms.

Chapter 3 explores the role of rod and cone photoreceptor pathway development on melanopsin levels in ipRGCs. In the mouse, rod and cone photoreceptor pathways are not fully developed until roughly postnatal day (PD) 10. Different ipRGC types are not evident at birth, and evidence obtained from two independent reporter mouse lines indicated that the separation of ipRGCs into two distinct types did not occur until PD 10. The development of M1 and M2 ipRGCs also is shown to depend on the daily light/dark cycle and dopaminergic neurotransmission.

In conclusion, the data presented in this dissertation indicate that there are two anatomically distinct ipRGC types in the mouse retina expressing differential amounts of melanopsin protein. Furthermore, the photoreceptors in the outer retina have a major role in regulating the amount of melanopsin protein that is present in ipRGCs. This regulation may be important for shaping the irradiance information that is relayed to the brain and used to synchronize circadian rhythms to the light/dark cycle and control pupil size.
Keywords: melanopsin; photosensitivity; retinal ganglion cells; neurobiology